Online updates: a column for search analysts. ITER -- International Toxicity Estimates for Risk, new TOXNET database. - Tomasulo P (Medical Reference Services Quarterly)
ITER, the International Toxicity Estimates for Risk database, joined the TOXNET system in the winter of 2004. ITER features international comparisons of environmental health risk assessment information and contains over 620 chemical records. ITER includes data from the EPA, Health Canada, the National Institute of Public Health and the Environment of the Netherlands, and other organizations that provide risk values that have been peer-reviewed.